SUFI HEALING COMMODIFICATION THROUGHOUT EAST JAVA URBAN ENVIRONMENTS - Huda, M. Syamsul (El-HARAKAH (TERAKREDITASI), 2020)
This article examines the shifting of the functions and motives of Sufi healing from the pesantren tradition, in which the main actor is the healer kiai who prioritizes community service and healing as part of the da’wah, changing to capital motives in conducting healing traditions in Islam. The research process used participatory observation method in clinical settings to examine Sufi healing practices and interview therapists and patients who use Sufi healing services, as well as comparative-historical methods in studying the ontology and epistemology of healing. The findings of this study include: first, Sufi healing contains elements of bayani, irfani, and finally bil kasbi. Yet, in practice it takes the irfani as the most common method, especially through the method of prayer, zikr, and prayer. Second, the integration built by Islamic therapists is done by combining medical method in the area of marketing share and psycho-sufism to build patient confidence. Third, this role is more than Sufi healing prioritizing the practice of religious capitalization, namely identifying medical treatment clinics in the form of Sufi healing for economic purposes. Artikel ini mengkaji pergeseran fungsi dan motif penyembuhan sufi dari tradisi pesantren yang aktor utamanya kiai tabib yang mengutamakan pengabdian kepada kesehatan dan penyembuhan masyarakat sebagai bagian dari dakwah, berubah ke motif kapital tradisi penyembuhan dalam Islam. Dalam proses penelitian menggunakan metode observasi partisipatif ke tempat klinik yang membuka praktek penyembuhan sufi dan mewawancarai terapis dan pasien yang menggunakan jasa penyembuhan sufi, serta menggunakan metode historis komparatif dalam menelaah ontologi dan epistemologi penyembuhan. Adapun temuan penelitian ini antara lain pertama, penyembuhan sufi memuat unsur bayani, irfani, dan terakhir bil kasbi. Namun dalam prakteknya cara irfani menjadi metode yang paling umum dilakukan, khususnya melalui metode do’a, zikir, dan salat. Kedua, integrasi yang dibangun para terapis islami adalah dengan cara memadukan antara cara medis pada wilayah pemasaran dan psiko sufistik untuk membangun keyakinan para pasien. Ketiga, peran ini lebih dari sufi healing yang mengutamakan praktik kapitalisasi agama, yakni mengidentifikasi klinik jasa pengobatan dalam bentuk penyembuhan sufi demi tujuan ekonomis.